Penyuluhan dan Pelatihan Pembuatan Pupuk Kompos Organik Pada Ibu-Ibu PKK Desa Gabahan RT 05 RW 12 Jombor Sukoharjo - Nur Rokhimah Hanik; Tri Wiharti; Ratna Dewi Eskundari (Universitas Mataram, 2022)
Residents of the village of Gabahan Rt. 05 Rw. Most of Jombor's 12 sub-districts work as farm laborers and hand laborers and desperately need additional income to meet the needs of their families. They have never received counseling or training on organic composting by universities or other institutions. From the results of the interview, several residents wanted counseling and training on the manufacture of organic compound fertilizer as an alternative to increase financial income. They want counseling with this theme because most of them do not understand how to make organic compost. The purpose of the service is 1. To provide counseling on how to make organic compost. 2. To provide training on how to make and pack organic compost. The training was carried out for 2 times. The method used is lectures and questions and answers, as well as practical guidance on how to make and pack organic compost. The target of this counseling and training is to increase the understanding of how to make 20% organic compost among the residents of Gabahan RT. 05 RW. 12 Jombor. From the results of the training in making organic compost for PKK women in the hamlet of Gabahan RT 05 RW 12 Jombor, it can be concluded that there was an increase in understanding of the process of making organic compost from an average score of 37.5 to 88.45 or an increase in understanding of 122, 4%. The results of the compost can be used by women as plant fertilizer, but can also be sold to increase income.